Ischemic Stroke at a Tertiary Academic Hospital in Tanzania: A Prospective Cohort Study With a Focus on Presumed Large Vessel Occlusion - Matuja, Sarah Shali; Ahmed, Rashid Ali; Munseri, Patricia; Khanbhai, Khuzeima; Tessua, Kezia; Lyimo, Frederick; Rodriguez, Gustavo J.; Gupta, Vikas; Maud, Alberto; Chaudhury, Mohammad Rauf; Manji, Mohamed; Sheriff, Faheem (Frontiers in Neurology, 2022)
Background: Large vessel ischemic strokes account for more than one-third of all strokes associated with substantial morbidity and mortality without early intervention. The incidence of large vessel occlusion (LVO) is not known in sub-Saharan Africa. Definitive vessel imaging is not routinely available in resource limited settings. Aims: We aimed to investigate the burden and outcomes of presumed LVO among ischemic stroke patients admitted to a large tertiary academic hospital in Tanzania. Methods: This cohort study recruited all consenting first-ever ischemic stroke participants admitted at a tertiary hospital in Tanzania. Demographic data was recorded and participants were followed up to 1-year using the modified Rankin Scale. A diagnosis of presumed LVO was made by a diagnostic neuroradiologist and interventional neurologist based on contiguous ischemic changes in a pattern consistent with proximal LVO on non-contrast Computed Tomography head. We examined factors associated with presumed LVO using logistic regression analysis. Inter-observer Kappa was calculated. Results: We enrolled 158 first-ever ischemic strokes over 8-months with a mean age of 59.7±16.6 years. Presumed LVO accounted for 39.2% [95%CI31.6%-47.3%] with an overall median time of stroke symptoms to hospital arrival of 1-day IQR [1-2]. Participants with presumed LVO were more likely to involve the middle cerebral artery territory 70.9%. Independent factors on multivariate analysis associated with presumed LVO were: hypertension aOR 5.74 (95% CI: 1.74 – 18.9) and increased waist-hip ratio aOR 7.20 (95% CI: 1.83 – 28.2). One-year mortality in presumed LVO was 50% compared with 37.5% in participants without presumed LVO (p=0.12). The Cohen’s Kappa inter-observer reliability between the diagnostic neuroradiologist and interventional neurologist was 0.847. Conclusion: There is a high burden of presumed LVO associated with high rates of 1-year mortality at a tertiary academic hospital in Tanzania. Efforts need to focus on confirming these findings with definitive vessel imaging, promoting cost-effective preventive strategies to reduce the burden of non-communicable diseases and a call for adopting endovascular therapies to reduce morbidity and mortality.